High Prevalence of Clonal Reproduction and Low Genetic Diversity in Scutellaria floridana, a Federally Threatened Florida-Endemic Mint - Gina Renee Hanko; Maria Therese Vogel; Vivian Negrón-Ortiz; Richard C. Moore (Plants, 2023)
The threatened mint Florida skullcap (Scutellaria floridana) is endemic to four counties in the Florida panhandle. Because development and habitat modification extirpated several historical occurrences, only 19 remain to date. To inform conservation management and delisting decisions, a comprehensive investigation of the genetic diversity and relatedness, population structure, and clonal diversity was conducted using SNP data generated by ddRAD. Compared with other Lamiaceae, we detected low genetic diversity (HE = 0.125–0.145), low to moderate evidence of inbreeding (FIS = −0.02–0.555), and moderate divergence (FST = 0.05–0.15). We identified eight populations with most of the genetic diversity, which should be protected in situ, and four populations with low genetic diversity and high clonality. Clonal reproduction in our circular plots and in 92% of the sites examined was substantial, with average clonal richness of 0.07 and 0.59, respectively. Scutellaria floridana appears to have experienced a continued decline in the number of extant populations since its listing under the Endangered Species Act; still, the combination of sexual and asexual reproduction may be advantageous for maintaining the viability of extant populations. However, the species will likely require ongoing monitoring, management, and increased public awareness to ensure its survival and effectively conserve its genetic diversity.